REKAYASA PROTEIN SUPEROKSIDA DISMUTASE Staphylococcus equorum REKOMBINAN, OVERPRODUKSI, DAN KARAKTERISASINYA - Triyanto, Bagus
Recombinant manganese superoxide dimutase Staphylococcus equorum (rMnSODSeq) exists as homodimer. Enzyme rMnSODSeq has moderate thermal stability with dimeric melting temperature (Tm) of 52°C. Three dimentional structure of rMnSODSeq shows that monomers interaction can be enhanced to improve dimer stability. This research aimed to increase the rMnSODSeq dimer structural stability by amino acid substitution and to study the effect of the substitution to its stability and activity. The research was initiated by in silico modelling using COOT program to determine the substitution site and the modelling resulted Glycine-125 to Threonin (G125T). Substitution of G125T was done at DNA level by site-directed mutagenesis of GG to AC of rMnSODSeq coding region in pJexpress414_sod using Polymerase Chain Reaction with two Single Primer IN Reaction Parallel. Mutation product was confirmed using sequencing and the desired mutation was successfully obtained using annealing temperature at 59°C. Overexpression of rMnSODSeq_G125T was performed at 37°C 150 rpm with IPTG induction at final concentration of 1 mM for 4 hours. Proteins were purified using affinity chromatography Ni2+ -NTA continued with anion exchange chromatography Q-Sepharose yielded pure protein. The pure protein was then characterized to determine its activity and dimer structural stability. Decreased activity of rMnSODSeq_G125T was observed by zymographic and colorimetric assay with specific activity reduction of 90.58% from 1730.3 U/mg (rMnSODSeq) into 162.96 U/mg (rMnSODSeq_G125T). The thermal shift assay showed that both proteins had Tm value of 58°C hence no difference in dimer structural stability. The G125T substitution of rMnSODSeq does not increase the dimer structural stability and causes reduction in protein specific activity.